Synthesis and structural characterisation of the lead-platinum sulfido aggregates [Pt2(μ-S)2(PPh3)4PbX2] (X = Br, I); promotion of rare tetrahedral geometry for lead(II) - Henderson, W. (2014)
10.1016/j.ica.2010.02.016